PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACES TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BATANG KAPAS - Afrona, Lina; Rahmi, Rahmi; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACT The purpose of this research was to describe the students learning activities and to reveal whether the mathematics conceptual understanding of the students taught by using Trading Place active learning strategy was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of SMPN 2 Batang Kapas registered in academic year 2013/2014. The instrument of the research were an observation sheet and an essay test. The data gathered was analyzed by using t-test assisted whit MINITAB. Based on the result of data analysis it was found that the two sample classes were normally distributed and homogenous. Furthermore, result of hypothesis test incated that p-value (0,007) was smaller than a signifying that the mathematics conceptual understanding of the student taught by using Trading Places active learning strategy was better than that of students taught by using conventional learning students in class VIII of SMPN 2 Batang Kapas.